Identification of Escherichia coli from potable water sources of Durg-Bhilai, Chhattisgarh (India), using 16S rRNA gene sequence Analysis - Mabel, Varghese; G, Roymon M (International Multidisciplinary Research Journal, 2013)
Potable water sources mainly municipal water and ground water (from tube wells) were studied for the presence of multidrug resistant pathogenic Escherichia coli. A total of 11 isolates were obtained, eight from municipal water and three from tube well water. Antibiotic resistance analysis (ARA) showed that only two strains named EcPH2 and EcPul2 isolated from municipal tap waters were multidrug resistant (MDR). The strains were characterized using 16S ribosomal RNA gene sequencing. Phylogenetic analysis and similarity search showed isolate EcPH2 had 98% similarity and EcPul2 had 94% similarity to E. coli. The 16S rRNA sequences were submitted to Genbank with accession no. KC254645, KC254646 for isolate EcPH2 and isolate EcPul2 respectively.